Achieving adjustable digital-to-analog conversion in memristors with embedded Cs2AgSbBr6 nanoparticles. Issue 16 (11th April 2023) - Wang, Yuchan; Xu, Nannan; Yuan, Yiming; Zhang, Wenxia; Huang, Qiang; Tang, Xiaosheng; Qi, Fei
Abstract : The digital-to-analog conversion of the memristor is realized by adjusting the embedding concentration of Cs2 AgSbBr6 nanoparticles. Abstract : In this work, the proportions of Cs2 AgSbBr6 nanoparticles (NPs) mixed in a PMMA film are adjusted to the digital and analog types of resistive switching (RS) behaviors in Ag/PMMA&Cs2 AgSbBr6 -NPs/ITO memristor devices. It is confirmed that when the concentration of NPs doped in the PMMA film is about 5 wt%, the memristor devices demonstrate bipolar digital RS behaviors with excellent electrical characteristics such as low operating voltage, high ON/OFF ratio (>500), good endurance (>800 cycles), and stable retention ability (>10 4 s). However, the devices showed a transition to analog-type memristive behavior when the concentration of NPs doped in the PMMA film is around 10 wt%, and several artificial synapse behaviors are successfully simulated. The device model simulation is also used to explore the effect of the NPs on the local electric field and growing filaments. Our work provides an opportunity to explore next-generation artificial synapse devices based on lead-free halide perovskites.